CLASSIFICATION AND CHARACTERISTICS OF IMPORT-EXPORT OPERATIONS AS ACCOUNTING OBJECTS - Khalikov Talibjon Luptullaevich (Antis Publisher, 2024)
Objective: The objective of this article is to examine the main principles and features of accounting for export-import transactions in the foreign trade activities of firms. It aims to explore the essence, types, and functions of cash flow in foreign trade transactions. Method: The article employs a descriptive approach to studying the stages of export-import transactions, their documentation, and accounting procedures. It also analyzes legislative changes affecting foreign trade transactions, emphasizing their implications for accounting practices. Results: The article outlines the key stages of export-import transactions and identifies the specific features of their documentary registration. It highlights how these transactions are structured and the cash flow functions they involve, contributing to a better understanding of foreign trade accounting. Novelty: The novelty of this research lies in its comprehensive review of the evolving regulations and their impact on the accounting practices of firms engaged in foreign trade. It provides a thorough exploration of export-import transactions' documentary requirements and accounting specifics within the context of recent legislative changes.